Imperativeness and Dimensions of Labour Welfare Measures for Employees’ Fulfilment in Manufacturing Companies of Chennai - Balaji, P.; Jagadeesan, P. (Prabandhan: Indian Journal of Management, 2019)
This empirical study was conducted to explore the fulfilment of labour welfare measures in selected manufacturing companies. Exploratory and descriptive research design was adopted to collect employees’ perceptions through a structured questionnaire by adopting non-random convenient sampling technique. The data collected were subjected to analysis using PSPP Version 1.0.1. The statistical tools such as percentage analysis, factor analysis, independent samples t - test, analysis of variance (ANOVA), and weighted average mean score were used in this study. The results indicated that fulfilment of welfare measures variables were reduced to seven independent factors, and the most dominant factor was found to be the Amenities Factor (AF) followed by Environment Factor (EF), Physical Well - Being Factor (PBF), Comfort Factor (CF), Yardstick Factor (YF), Food Factor (FF), and Supervision Factor (SF) in their order of dominance. We concluded that employees gave importance to counselling facilities, transport facilities, medical facilities, and housing facilities in order of importance to enhance their satisfaction levels.